The dilemma of Hudud and international human rights: proposing a benevolent mechanism - Ismail, Shahrul Mizan (2007)
Ever since the emergence of the international regime of human rights, the irresolvable dilemma has always been to draw an effective reconciliation between the theocentric essentials of Islamic law and the demands of International Human Rights Law. This problem is further exacerbated in the case of Islamic criminal punishments, especially Hudud1 because unlike Ta’zir2 , where the offences are not prescribed and the punishments are neither fixed nor quantified by the Quran and Sunna, the Hudud punishments are clearly laid down for offences which have been explicitly stated by the two highest sources of Islamic criminal law, namely the Quran and Sunna. 3 And different from Qisas,4 where punishments though clearly prescribed, aims purely to secure the rights of man, (which consequently allows the victim or his legal heirs to alter or remit the punishments), Hudud penalties were formulated to secure the rights of God hence it is often argued that no one but God, himself may “forgive the crime or change the law” The fact that it involves the right of God signifies that it is meant to be mandatory punishment, a demand from God that requires fulfillment and no one, including the victim, judge or the head of state has authority to alter or modify, what more to pardon or suspend it. Due to these reasons, Muslim countries are usually of the view that the enforcement of such punishments is a non-negotiable religious obligation. Human rights activists on the other hand, argued that the implementation of the Hudud laws contravenes multiple norms and values of international human rights law. Ever since then, there have been many attempts to stop the aforesaid violations by stopping altogether the implementation of Hudud punishments in numerous Muslim countries. The writer contends that the current, typical approaches adopted in international human rights law in attempting to prevent further violations of human rights in this respect, is ineffective, insensitive and had contributed even further in worsening the problem of human rights violation in relation to the implementation of Hudud punishments in Muslim countries. This paper aims to analyze critically, the weaknesses inbuilt in the typical approaches adopted by human rights advocates in dealing with the issue of human rights violations relating to Hudud law.